Detection of Fetal Aneuploidies by QF-PCR in Transcervical Cell Samples. (23rd December 2012) - Cioni, Riccardo; Bussani, Cecilia; Di Tommaso, Mariarosaria
Abstract : Objective . To evaluate the accuracy in the diagnosis of aneuploidies of a quantitative fluorescent polymerase chain reaction (QF-PCR) assay on trophoblastic cells recovered from transcervical cells samples (TCCs) collected by intrauterine lavage (IUL). Study Design . DNA analysis was performed on cells of seemingly trophoblastic origin isolated from IUL samples collected prior to first trimester termination of pregnancy. The analysis was performed by multiplex QF-PCR, using a panel of 29 polymorphic short tandem repeats (STRs) for the chromosomes X, Y, 21, 13, and 18. Results . The QF-PCR analysis on placental samples revealed that among the three cases studied there were two cases of trisomy 21 and one case of monosomy X; the comparison of peak profiles obtained from IUL, placental, and maternal samples confirmed the diagnosis of aneuploidy in all three cases. Conclusion . This study suggests that the detection of chromosomal aneuploidies in micromanipulated TCC samples can be achieved by QF-PCR amplification of selected highly polymorphic and chromosome specific markers. With respect to standard karyotype, QF-PCR analysis has the limitation that only numerical abnormalities of selected chromosomes can be detected but retains the advantages of being quicker, less expensive, and less lab demanding.